2008
DOI: 10.1021/jm800719t
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Conjugates of 7-Ethyl-10-hydroxycamptothecin (SN-38) for Targeted Cancer Chemotherapy

Abstract: CPT-11 is a clinically used cancer drug, and it is a prodrug of the potent topoisomerase I inhibitor, SN-38 (7-ethyl-10-hydroxycamptothecin). To bypass the need for the in vivo conversion of CPT-11 and increase the therapeutic index, bifunctional derivatives of SN-38 were prepared for use in antibody-based targeted therapy of cancer. The general synthetic scheme incorporated an acetylene-azide click cycloaddition step in the design, a short polyethylene glycol spacer for aqueous solubility, and a maleimide gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 26 publications
2
119
0
1
Order By: Relevance
“…Although the more recently approved ultratoxic ADCs use linkers that bind the drug stably while in serum, as premature release of those agents would increase toxicity and reduce their therapeutic window, our in vivo experience revealed the optimal therapeutic activity for an SN-38 ADC required a linker that neither held the drug stably nor released it too early (9,10,21). This conjugate system also permits the site-specific coupling of nearly 8 molecules of SN-38 per IgG without affecting the physiochemical nature, immunoreactivity, or the pharmacokinetics of the conjugate compared with unconjugated IgG (12).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the more recently approved ultratoxic ADCs use linkers that bind the drug stably while in serum, as premature release of those agents would increase toxicity and reduce their therapeutic window, our in vivo experience revealed the optimal therapeutic activity for an SN-38 ADC required a linker that neither held the drug stably nor released it too early (9,10,21). This conjugate system also permits the site-specific coupling of nearly 8 molecules of SN-38 per IgG without affecting the physiochemical nature, immunoreactivity, or the pharmacokinetics of the conjugate compared with unconjugated IgG (12).…”
Section: Discussionmentioning
confidence: 96%
“…Selecting the best conjugate relied on efficacy studies in human tumor xenograft/mouse models, with the linker designation CL2 providing the best responses (9,10). Interestingly, in vitro serum stability studies of the initial 3 candidate conjugates revealed that SN-38 was released at different rates, with one having a half-life of about 10 hours, whereas another was highly stable; yet, the selected CL2-linked conjugate had an intermediate stability in serum of 36 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Assays used to compare cell binding of the unconjugated and conjugated milatuzumab with antigen-positive cells, and cytotoxicity testing using the MTS dye reduction method (Promega), have been reported previously (27).…”
Section: In Vitro Cell Binding and Cytotoxicitymentioning
confidence: 99%
“…Because a milatuzumab-doxorubicin conjugate was highly active in models of hematologic tumors (13,14), it was a logical choice for this assessment. However, we developed procedures for coupling the highly potent topoisomerase I inhibitor, SN-38, to antibodies (26,27). SN-38 is the active form of irinotecan, whose pharmacology and metabolism are well known (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…These derivatives of SN38 were synthesized according to the reported references with modifications. [33][34][35] SN38 (1 g, 2.55 mmol) and DIBOC (0.61 g, 2.81 mmol) were stirred in anhydrous dichloromethane (DCM) with a catalytic amount of anhydrous pyridine for 14 hours at room temperature. The reaction mixture was then washed several times with 0.5% NaHCO 3 and 0.1 mol/L HCl.…”
Section: Animals and Cell Linementioning
confidence: 99%